Effect of Self-Efficacy Enhancing Education Program on Family Caregivers’ Competencies in Caring for Patients with mild Traumatic Brain Injury in Yogyakarta, Indonesia - Firmawati, Erfin; Songwathana, Praneed; Kitrungrote, Luppana (Department of Nursing, Faculty of Medicine, Diponegoro University, 2014)
Purpose: This study was conducted to examine the effect of a self-efficacy enhancing education program on family caregivers’ competencies regarding perceived confidence and performance in caring for patients with mild TBI in Yogyakarta, Indonesia. Methods: The quasi-experimental study, two groups pre-test and post-test design was conducted. Fifty family caregivers and patients with mild TBI who met the inclusion criteria were recruited. The first 25 control group received the routine care were, while another 25 subjects in the experimental group received a self-efficacy enhancing education program developed by the researchers. The program was constructed using Bandura’s four sources of self-efficacy. The family caregivers’ perceived confidence and performance were measured by using the Perceived Confidence Questionnaire (PCQ) and the Performance Questionnaire (PQ). The data were analyzed using paired t-test, independent t-test, Wilcoxon Signed Rank test, and Mann-Whitney U test. Results: The findings showed that the family caregivers who participated in the program had a higher in perceived confidence (t = 8.30, p < .05) and performance (U = .00, p < .05) in caring for patients with mild TBI upon the completion of the program. Conclusion: This study suggests the program may have contributed in improving the family caregivers’ competencies regarding perceived confidence and also influencing their performance in caring for patients with mild TBI. Therefore, this program is recommended for nurses to extend this knowledge for nursing practices and improve family caregivers’ competencies in caring for patients with mild TBI before and after discharge.